Eruptive acral lentiginosis following chemotherapy for acute lymphoblastic leukemia: A case series - Cathal O’Connor (Wiley, 2021)
Abstract Lentigines are brown macules which develop due to increased proliferation of melanocytes at the dermo‐epidermal junction. We report three cases of acral lentiginosis in children following chemotherapy for acute lymphoblastic leukaemia (ALL) which have persisted following cessation of chemotherapy, despite avid photoprotection. Generalised eruptive naevi with subsequent development of dysplastic naevi and melanoma in situ have been reported following chemotherapy, highlighting the importance of continued clinical observation.